Developing an Android-Based Online Football News Application Using News API for CV Cipta Rasendriya - Bagas Tri Prakoso; R Soelistijadi; Taufiq Dwi Cahyono (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Football is the most popular sport in the world with 4 billion fans, including in Indonesia which has the largest fan base. In the digital era, the majority of soccer fans access news via mobile devices because it is more practical than print media. However, limited access that requires users to open several websites to obtain the latest information is an obstacle. CV Cipta Rasendriya, as a football media that focuses on YouTube channels, took the initiative to develop an Android-based football news application. This application aims to make it easier for fans to access the latest news through the integration of the News API which displays real-time news from various trusted sources. Application development is carried out using the System Development Life Cycle (SDLC) Prototyping model, which was chosen because of its advantages in understanding user needs, flexibility to change, and cost efficiency. The results of application testing using the black box method showed a 100% success rate in the main test scenarios, such as news search, current news display, and navigation between pages, all of which functioned as expected. In addition, the UEQ test results showed that the application scored very well on the dimensions of Clarity (2.06), Efficiency (2.03), Attractiveness (1.92), Stimulation (1.81), and Novelty (1.69), as well as a good score on the dimension of Accuracy (1.59). The app provides more benefits than conventional methods by integrating various news into one platform, with a search feature to make it easier for users to find their favorite club news. In addition, this application has the potential to improve the user’s experience in accessing football news in a practical, fast, and relevant manner